Exploration of the Gesek Godong Leaf-Transfer Technique for Textile Pattern Creation Using Wooden and PVC-Based Tools - Maria Jesica Chinta Putri Arumdhani; Romadhona Chusna Tsani (An International Journal Tourism and Community Review, 2026)
Textile motifs are works that employ designs created through various techniques. One method of creating textile motifs is the gesek godong technique. This technique is a traditional method in textile design that uniquely uses dried leaves as natural materials to transfer leaf patterns. In this study, the gesek godong technique will be developed using different tools: a wooden rolling pin, a wooden cutting board, and PVC pipe. This study aims to explore the creation of innovative and creative textile motifs using the gesek godong technique. It also seeks to understand the process of creating textile motifs through the gesek godong method using the 4D R&D approach. The findings show that the gesek godong technique can be used to create unique and appealing textile motifs, using leaves as the primary material and different rubbing tools such as a wooden rolling pin, wooden cutting board, and PVC pipe. In addition, this study also discusses how to use each of the rubbing tools. The results from each tool show distinct outcomes, each producing motifs with their own unique quality. In applying the gesek godong technique, one can also select leaves with thick veins to achieve well-defined motifs. In addition to using leaves with thick veins, the coloring technique should avoid excess moisture, so the dye does not spread too much.